2013
DOI: 10.2478/s11535-013-0267-9
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition of the leaves of Reynoutria japonica Houtt. and soil features in polluted areas

Abstract: Abstract:The study was conducted on six sites that are dominated by Japanese knotweed (Reynoutria japonica) and that vary in the level of industrialization and habitat transformation by humans. The aim of the research was to investigate the chemical-physical features of soil under a closed and dense canopy of R. japonica, the chemical composition of the R. japonica leaves, and to compare the content of certain elements in the soil-plant-soil system. The soil organic carbon (C org ) content varied from 1.38±0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
31
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 47 publications
8
31
2
1
Order By: Relevance
“…With reference to the above, it can be stated that F. japonica is the most tolerant to high nitrogen variation in soil when compared to the remaining knotweed species. Concerning organic carbon, in our study soils were not very rich, as in the Belgium sites [36], but ours were more similar to the results obtained by Rahmonov et al [45] for F. japonica. Furthermore, the concentration of phosphorus in our soils was very variable as in sites in Belgium [36].…”
Section: Tabsupporting
confidence: 91%
See 2 more Smart Citations
“…With reference to the above, it can be stated that F. japonica is the most tolerant to high nitrogen variation in soil when compared to the remaining knotweed species. Concerning organic carbon, in our study soils were not very rich, as in the Belgium sites [36], but ours were more similar to the results obtained by Rahmonov et al [45] for F. japonica. Furthermore, the concentration of phosphorus in our soils was very variable as in sites in Belgium [36].…”
Section: Tabsupporting
confidence: 91%
“…6.5., whereas in wasteland in Belgium it varied between 4.9 to 7.4 [36]. Also Rahmonov et al [45] showed that sites invaded by F. japonica are very diverse in pH, from 4.0 to 7.5.…”
Section: Environmental Requirements Of Fallopia Taxa and Accompanyingmentioning
confidence: 99%
See 1 more Smart Citation
“…One study was conducted by Soltysiak et al (2011) in the Central European cities of Wroclaw and Prague, but it evaluated only five heavy metals (Cr, Cd, Fe, Pb and Zn). Previous studies mainly investigated different ecological and physicochemical characteristics of R. japonica (Nishizono et al 1989;Rahmonov et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Human activities have intensified the release of P by the year 2000; the global mobilisation of the nutrient had roughly tripled compared to its natural flows: increased soil erosion and runoff from fields, recycling of crop residues and manure, discharges of urban and industrial wastes, and, above all, application of inorganic fertilisers were the major causes of this increase (Smil 2000;Rahmonov et al 2014). An important element in the cycle and migration of phosphorus is the type of catchment management in relation to the annual outflow of phosphorus.…”
Section: Resultsmentioning
confidence: 99%